Classificação de risco em saúde mental: implicações clínicas, éticas e sócio-políticas - Paula, George Luiz Costa de (2019)
The present study aims to critically analyze the processes of risk classification in mental health and its clinical, ethical and socio-political implications. It also intends to understand the evolution of the concept of risk and its applications in different areas of knowledge, analyzing the daily routine of mental health services regarding the use of care protocols to users. This is a study of qualitative and exploratory-documental approach. The field of study was the city of Sobral-CE and the scenario of study the network of Integral attention to Mental Health of Sobral (RAISM) in its two main services: the Psychosocial Care centers (CAPS II and AD). The scenario also included two devices belonging to the primary health care (PHC): The Family Health Center Professor Norma Soares (CSF Alto da Brasília) and the coordination of APS in the municipality of Sobral. The study participants were 7 subjects, divided among managers, professionals and users of the institutions contemed. We used as techniques for data collection The Documental research and participant observation, as well as semi-structured interview, composed of a questionnaire elaborated by the researchers, being the same recorded and performed by signing the term of Free and informed consent. Data were treated through categorization and thematic analysis after transcription of the interviews. The results of the study pointed to the division of risk into four thematic categories: concept, work processes, applicability and professional-user relationship. Linked to each of these, the existence of different thematic subcategories was also evidenced. In the concept, the risk was shown as criterion for decisions, work resource and trigger of care, fundamental characteristics for the demands of professionals and health services. In work processes, assistance and intersectoral work were considered as two possible fields, within which the main consequences of care happen. Regarding the applicability, the Mental Health Risk Stratification Questionnaire (QERSM) proved to be the main instrument. This was characterized by allowing ample multiprofessional access to its application, continually needing a process of evaluation and monitoring of the effects generated by its use. Finally, in the relation, it was observed that the adoption of questionnaires does not interfere in the subjective relationship between professionals and users, being the same beneficial to the services they use. Through this research, it is concluded that the risk classification has several developments, being used much more as an auxiliary resource in the work process than in the labeling of the subjects. It was observed the existence of a necessary effort to approximate the professionals of the stratification instrument and to foster the dialogue between primary and secondary attentions. It was also concluded that the subjectivity of relations in health does not happen through the unique application of questionnaires and related instruments. Finally, the study allowed access to the concrete reality of mental health services, representing a critical picture of a local context, bringing equally important elements of social responsibility.